Improving seismic behavior using a hybrid control system of friction damper and vertical shear panel in series. (June 2021) - Zare Golmoghany, Mohsen; Zahrai, Seyed Mehdi
Abstract: In this paper to improve the seismic behavior of structures and decrease structural earthquake damages, a new hybrid control system is proposed consisting of Friction Damper and Vertical Shear Panel (HFD-VSP) in series. The new system benefits of two-level energy dissipation such that in moderate earthquakes friction damper (FD) as the first fuse operates while in strong earthquake both FD and Vertical Shear Panel (VSP) dissipate energy. FD can eliminate the shortcoming of VSP in terms of ductility and low cycle fatigue. FD and VSP are modeled in ABAQUS and related numerical results are compared to those of previous experimental studies for verification purposes. Pushover and cyclic loadings are conducted for two models. The hysteresis curves show symmetric two-level behavior with stable strength and stiffness by increasing the ductility ratio of 87.3%. To study the performance of the HFD-VSP, seismic analysis and incremental dynamic analysis, IDA, are applied to two 5-story buildings with and without hybrid dampers. Maximum drift and maximum roof displacement decrease by 17.4% and 17.1% on average under earthquakes. Average IDA results show that first mode spectral acceleration at HFD-VSP is 1.14 times that of the frame with just VSP. The drift and spectral acceleration of the collapse prevention level increase 33.3% and 28%. The proposed system using FD and VSP performed better than the vertical shear panel against an extensive range of earthquakes as well as the mainshock with strong foreshocks and aftershocks.